Pendampingan Majelis Al-Fikr melalui Program Kitab Jurumiyah dan Diskusi Ilmiyah pada Santri Ponpes Sunan Drajat Lamongan - Zakiyatul Abidah; Sutopo Sutopo; Muhammad Habibur Rohman; Muzzammil Muzzammil; Duroril Fahmi (KERIS : Journal of Community Engagement, 2022)
The Jurumiah Book, is one of the reference books in Arabic grammar learning which is commonly used in Islamic boarding schools. All students are required to learn Arabic grammar as a basis for their ability to read the yellow books which are the references in learning at the Islamic boarding school. The focus of this research relates to the preparation of qawaid learning materials in the Jurumyiah book. This study aims to describe the composition of the qawaid nahwiyah learning material in the al-jurumyiah book written by ibn needle or known as ash-shanhaji. This research is descriptive quantitative research using content analysis method. The results of the study show that the Jurumyah book is included in the group of conceptual types of material. The preparation of the material is in accordance with the principles of material development and is adaptable to changes in the learning paradigm that emphasizes the activeness of students (santri) who study it.